1983
DOI: 10.1021/bi00276a026
|View full text |Cite
|
Sign up to set email alerts
|

Release of [3H]adenosine cyclic 3',5'-phosphate bound to the regulatory moiety of protein kinase I in the presence of magnesium(2+), ATP and the catalytic subunit of the kinase

Abstract: The rate of release of bound c[3H]AMP from the two types (A and B) of cAMP binding sites on the regulatory subunit dimer (R2I) of rabbit muscle protein kinase I was studied in the presence of the catalytic (C) subunit of protein kinase. Rebinding of released c[3H]AMP was avoided by using highly diluted reactants or adding unlabeled cAMP or its analogues. No significant C-induced dissociation of R2I-(c[3H]AMP)4 occurred in the absence of Mg2+-ATP. Of the two options that one or two molecules of C are required t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
17
0

Year Published

1991
1991
2015
2015

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 33 publications
(17 citation statements)
references
References 46 publications
0
17
0
Order By: Relevance
“…Kinetic evidence [22] as well as results from cAMP binding site mutants [10] and cAMP analogs [25,26] have indicated that kinase activation is mediated via a sequential kinetic mechanism. First, cAMP The cAMP analogs are listed according to their R l A/B selectivity [5].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Kinetic evidence [22] as well as results from cAMP binding site mutants [10] and cAMP analogs [25,26] have indicated that kinase activation is mediated via a sequential kinetic mechanism. First, cAMP The cAMP analogs are listed according to their R l A/B selectivity [5].…”
Section: Discussionmentioning
confidence: 99%
“…1 and Table 1 the two cAMP binding sites in the wild-type R I subunit are readily distinguished by their cAMP dissociation rates. The rapid dissociation (kon-= 1.0 min -1) represents the exchange of cAMP bound to site A while the slower dissociation (kofr = 0.0167 min -]) is the exchange from site B [22]. Dissociation rates were measured with high salt in the buffer, a condition known to emphasize biphasic exchange [23].…”
Section: Purification and Camp-bindingmentioning
confidence: 99%
“…It is known that addition ofthe C subunit causes the release of cAMP from the R-cAMP complex with either RI and RII (22,29,30). Mutant RII provided a suitable means for testing whether or not the effect of the C subunit on cAMP dissociation is due to the interaction ofthe C subunit with the hinge region.…”
Section: Resultsmentioning
confidence: 99%
“…The cAMP binding capacity of RII was measured with a Millipore filtration method described by D0skeland and Ogreid (25). The reaction mixture contained 2 ,uM [3HJcAMP (25)(26)(27)(28)(29)(30) Ci/mmol; 1 Ci = GBq), 50 mM potassium phosphate (pH 6.8), 1 mM EDTA, type IIA histone (Sigma) at 0.5 mg/ml, 2 M NaCl, and 1 Ag of RII. The binding reaction was carried out at 30'C for 30 min and terminated by adding ice-cold 95% (wt/vol) ammonium sulfate solution.…”
mentioning
confidence: 99%
“…Consequently, PDE7A1 can play a dual role in promoting PKA holoenzyme re-association following hormonal stimulation-localization of C to the vicinity of R/cAMP dimers and elimination of cAMP as it is released from R. R dimers compete effectively for binding with C pre-bound to PKI, and potentially also with C pre-bound to PDE7A1 (44). The binding of C to R/cAMP dimers facilitates cAMP dissociation, a rate-limiting step in PKA re-association (45)(46)(47). Cyclic AMP release from R is inhibited by physiological concentrations of cAMP (1 M), and rapid cAMP hydrolysis upon its release facilitates the release of the additional three cAMP molecules bound to R/cAMP and the consequent re-association of PKA.…”
Section: Discussionmentioning
confidence: 99%